Evaluation of Honey Production for Industry Purposes, The Case of Beekeeping with Apis Mellifera in Indonesia After The Covid-19 Pandemic - Purwanto, Didik B.; Kuntadi, Kuntadi; Adalina, Yelin; Meilin, Araz; Raffiudin, Rika; Sahlan, Muhamad (International Journal of Social Service and Research, 2024)
The Indonesian beekeeping industry, grappling with diverse bee species, focuses on the sustainability of operations, particularly with the introduction of Apis mellifera during the early stages of the pandemic. This study explores post-pandemic Apis mellifera honey production in Indonesia, analyzing its impact on prices and business sustainability. Surveys and interviews were conducted with beekeepers in Java and Sumatra, primary islands with significant A. mellifera activities, along with data collection from other regions from January 2022 to October/November 2023. Monthly observations centered on honey production and prices for industrial purposes. The study uncovered two beekeeping systems: migratory in Java and stationery in Sumatra. Carpa honey from Accacia crassicarpa plantation emerged as a suitable industrial honey, displaying sustainable production, seasonality, and a large carpa area as bee forages, contributing to colony growth. Conversely, four Java honey types showed lower productivity, indicating a potential absence of honey seasons. Carpa honey prices ranged from IDR 25,200 to IDR 31,000 per kg, influenced by market size, production, competition, productivity, costs, and producer-consumer interactions. Despite a pandemic-induced surge in the honey market, sustaining high productivity and increasing colony numbers are crucial for long-term honey production sustainability.